Economics of Alternative Incubation Technology in the Development of Subsistence Poultry Enterprise: Evidence Involving Indigenous Knowledge in Katsina State, Nigeria - Ugwu, S.O.; Onyimonyi, A.E.; Ozor, Nicholas; Mkpado, M. (International Journal of Poultry Science, 2009)
The study examined sound reasons, principles and techniques employed by subsistence farmers in the art of masterminding Nigerian native hens to incubate, hatch and brood guinea fowl chicks in Katsina State of Nigeria. Ninety subsistence poultry farmers were randomly selected without replacement from the three agricultural zones of the state. Sources of primary data were structured questionnaires, market survey and observations of field activities and interviews. Descriptive statistics, Kolmogorov-Smirnov (K-S) one sample statistics and gross margin analysis were employed in data analyses. Results showed that lack of technical know-how on incubator operations and the breeding of exotic birds, poor capital base and the broodiness of the Nigerian native hens, were the major reasons for farmers adoption of the indigenous technology. Further results showed that 33% and 39% of the farmers each can produce 3,250 and 2,200 guinea fowl eggs respectively per breeding season of about four months per annum. A gross margin of Niara 5875.00 per Nigerian native hen was obtained from the analysis. The paper concludes with emphasis on the need for mass adoption of the indigenous technology by other small-holder farmers in the country because it is economical. This can be achieved through vigorous awareness campaigns on the technology by development agencies that are interested in bettering the living standards of the rural populace